2023
DOI: 10.7150/ijbs.80256
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor 4 Attenuates Neutrophilic Airway Inflammation in Experimental Asthma via Repressing Proinflammatory Macrophage Activation

Abstract: Patients with eosinophilic asthma react well to conventional treatment of asthma while individualized therapy for non-eosinophilic endotypes have yet to be developed. Dysregulated sphingosine metabolites are associated with the pathophysiology of different asthma endotypes with their receptors involved. However, whether the sphingosine-1-phosphate receptor 4 (S1PR4) contributes to disease progression of asthma remains underappreciated. In this study, we demonstrated that sphingosine metabolism was disturbed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Similarly, Megumi et al found that licochalcone A (39) inhibited IKK complex activation and IκB degradation via the covalently binding to amino acid residue Cys179 of IKKβ [159]. Additionally, some of dihyflavones, such as erioddictyol (40), naringenin (41), and pinocembrin ( 42), could interact with amino acid residues Thr23, Glu97, Cys99, and Asp166 in the ATP binding domain through hydrogen bonds to suppress the IKKβ activity [160].…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Megumi et al found that licochalcone A (39) inhibited IKK complex activation and IκB degradation via the covalently binding to amino acid residue Cys179 of IKKβ [159]. Additionally, some of dihyflavones, such as erioddictyol (40), naringenin (41), and pinocembrin ( 42), could interact with amino acid residues Thr23, Glu97, Cys99, and Asp166 in the ATP binding domain through hydrogen bonds to suppress the IKKβ activity [160].…”
Section: Flavonoidsmentioning
confidence: 99%
“…IKKβ-mediated NF-κB pathway is a key signal transduction pathway involved in inflammatory response, angiogenesis, invasiveness, metastasis, and immune escape [39][40][41][42][43][44][45][46]. After this signaling pathway is activated by inflammatory factors, it promotes the expression of inflammatory factors at the transcriptional level as well, thus forming a loop and producing an amplification effect to aggravate inflammation response [47][48][49][50][51].…”
Section: The Ikkβ Mechanismmentioning
confidence: 99%
“…However, there is limited and controversial information about the mechanisms controlled by S1PR4. S1PR4 may participate in the release of proinflammatory cytokines in activated macrophages and mediate the activation and maturation of dendritic cells [ 156 ], but also its absence exacerbates M1 polarization and pulmonary inflammation [ 157 ].…”
Section: S1p and The Immune Systemmentioning
confidence: 99%